Internal Fixation And Bone Grafting Of Non-Union Humeral Diaphyseal Fracture - Al-assadi, Tarik k. (AL-Kindy College Medical Journal, 2013)
Background: Humeral diaphyseal fracture usually heals with closed methods but when nonunion develops then it needs surgical intervention in the form of plating and bone grafting, intramedulary nailing (open or closed simple or interlocking nails) and external fixators (circular or one plane fixator). In our unit we treated non union humeral diaphyseal fracture with plating and bone grafting shortening of fracture ends up to 4 to 5cm when needed. Methods: This study was conducted at Orthopaedic Department of AL-Sadar General Hospital from January 2004 till December2005 . We included 20 cases with atrophic non-union in 12(60%) and hypertrophic non-union in 8 (40%) patients. All atrophic non-union were treated with plating, bone shortening by transverse osteotomy and bone grafting, while hypertrophic non-union were treated with decortications of non-union ends and fixation with compression plates, with bone grafting in old age. Follow up measures were based on clinical (range of joints motion) and radiological (healing) findings. Follow up was done for upto 6 months . Results: Out of 20 patients the age range was 20- 60 years, 16 (80%)were male and 4(20%) female. Right humerus involved in 15( 75 %) while left humerus in 5( 25%) patients. In12(60%) patients with atrophic non union bone shortening by transverse cut osteotomy was done while in remaining patients with hypertrophic nonunion plating was done in 2( 10 %) cases and plating with bone grafting in 6( 30%) patients. Union was achieved in all patients after 16 to 20 weeks of surgery. In one patient ( 5 %) of 75 years age with hypertrophic non-union implant was loosened after 3 months of surgery. At that time healing (Union) was evident on X-rays and humeral brace was applied for further 3 months. Two patients( 10 %) got neuropraxia of radial nerve which resolved with in 3 months time. 2 patients (10 %) developed shoulder stiffness which resolved after exercise. Conclusion: In Non Union of Humerus shortening by transverse osteotomy & rigid fixation with plates give excellent results in selected cases.